Research of the domestic market of drugs for the treatment of HIV infection - T. P. Zarichna; T. S. Brytanova (Zaporozhye State Medical University, 2023)
The aim of the research is to study the domestic market of medicines for the treatment of HIV infection to optimize the drug supply of the target group of patients. Materials and methods. Electronic sources of information (State Register of Medicines of Ukraine, Compendium-online, Tabletki.ua) were used to achieve the goal. System-analytical, mathematical-statistical, and comparative methods of analysis were used. Results. The study of the assortment of drugs for the treatment of HIV infection showed the heterogeneity of the specified segment of the pharmaceutical market of Ukraine: there are solid and liquid dosage forms, both original and generic. The analysis of the company structure made it possible to establish that the national market of drugs for the treatment of HIV infection was dominated by foreign manufacturers (95.93 %), the largest share of which was pharmaceutical companies from India (67.07 %). The competitiveness of pharmaceutical firms supplying drugs for the treatment of HIV infection was studied. It was established that the firm Janssen-Silag S.p.A., Italy, occupied the most stable position in the studied market segment. A qualitative analysis of the mentioned medicines was carried out. The most effective and rational of them were determined. Conclusions. A study of the domestic market of drugs for the treatment of HIV infection was conducted. The assortment and brand structure of this market segment was determined. The level of competitiveness of the above-mentioned pharmaceutical companies were analyzed, and the most successful of them were identified. At the same time, it was established that domestic pharmaceutical companies supply only 4.07 % of drugs of two out of five groups according to the ATS classification to this segment of the market. In connection with this, the development of new drugs of the specified action and the development of their production in Ukraine is important.